2019
DOI: 10.1002/ncp.10237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Implementation of the American Society for Parenteral and Enteral Nutrition Model for Parenteral Nutrition Order Writing and Review on Competency, Attitudes, and Perceptions

Abstract: Background: The American Society for Parenteral and Enteral Nutrition (ASPEN) parenteral nutrition (PN) safety consensus recommendations advise a comprehensive education program and competency assessment for all healthcare professionals involved in the care of patients receiving PN. The ASPEN-model papers provide guidance for designing PN competencies for prescribers, pharmacists, and pharmacy technicians. The purpose of this research was to evaluate the impact of a comprehensive educational program that align… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
1
8
0
3
Order By: Relevance
“…16,24 Preexisting epistaxis was considered as contraindication in those studies. 25 In the light of the high-risk constellation for severe bleeding events in our cohort, the risk of severe bleeding was negligible to little when using CEAS for establishing nasojejunal EN. Clearly, a relatively high overall rate of epistaxis was noted in these high-risk patients but at a low grade (CTCAE grade 1, 37.5%).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…16,24 Preexisting epistaxis was considered as contraindication in those studies. 25 In the light of the high-risk constellation for severe bleeding events in our cohort, the risk of severe bleeding was negligible to little when using CEAS for establishing nasojejunal EN. Clearly, a relatively high overall rate of epistaxis was noted in these high-risk patients but at a low grade (CTCAE grade 1, 37.5%).…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, transportation of ICU patients to another department for the intervention may compromise patients safety, ultimately resulting in more operation time be required or postponement of the intervention. 6,24,25 With this analysis, we are the first to show that the use of electromagnetic-guided CEAS for PP feeding tube placement is feasible, safe, and effective in patients with a low platelet count and receiving therapeutic anticoagulation in the ICU. Beside such a highly selected study population, CEAS has proven efficacy and safety in numerous studies when performed by an experienced operator.…”
Section: Discussionmentioning
confidence: 96%
“…The average score for nutrition support was 3.05 out of a maximum of 5, which was lower than their biostatistics and pharmacokinetics scores [6]. In another study, only 39.5% of the pharmacists at the beginning of a continuing education course indicated that they felt comfortable calculating protein and caloric requirements for patients on PN [7].…”
Section: Introductionmentioning
confidence: 86%
“…The literature suggests that pharmacists may not be adequately prepared to provide direct patient care in the area of nutrition support [6,7]. For example, in a study by Mutz et al, pharmacy residency directors were asked to evaluate their postgraduate year one (PGY1) residents' clinical knowledge [6].…”
Section: Introductionmentioning
confidence: 99%
“…According to a survey sent to ASHP‐accredited pharmacy postgraduate year one (PGY1) residency directors in the United States, residents scored the lowest in their clinical knowledge of nutrition compared to all other domains, including pharmacokinetics and biostatistics 13 . Furthermore, approximately 37% of pharmacists reported a lack of confidence in calculating energy and protein needs of PN patients 14 . In addition, a survey conducted by Sheridan et al evaluated pharmacists' education and responsibilities in PN and was sent to members of the American College of Clinical Pharmacy (ACCP) Critical Care Practice and Research Network 15 .…”
Section: Introductionmentioning
confidence: 99%